Breaking the Silence; Reproductive and Sexual Health of Women Undergoing Hemodialysis, A Literature Review - Zafar, Misbah; Jan, Rafat; Rattani, Salam; Chagani, Sajida (Pakistan Journal of Kidney Diseases, 2024)
As the basis for the continued existence of the human race, sexuality is a crucial aspect of human life. If this special aspect of human life is disturbed, it can hurt one’s self-confidence and self-esteem and negatively impact social and marital relationships. Given the significance of sexuality, sexual and reproductive health is regarded as a fundamental human right and a crucial element of general health. However, sexual and reproductive health issues appear to be very common in chronic kidney disease (CKD) patients, particularly among women on hemodialysis. The common sexual and reproductive health issues identified among women in literature are hypoactive sexual desire, pain, infertility, menstrual disturbances. These issues impact their marital lives and quality of life. Regardless of the fact that women undergoing hemodialysis face numerous challenges, healthcare professionals often overlook this important aspect of their lives and they are not counselled about the maintenance of their sexual and reproductive health. In Pakistan, there is dearth of literature exploring sexual and reproductive health issues of women undergoing hemodialysis so there is a need to investigate this area of concern.